Addressing the Needs of Diverse Distributed Students - Shimoni, Rena; Barrington, Gail; Wilde, Russ; Henwood, Scott (International Review of Research in Open and Distributed Learning, 2013)
Two interrelated studies were undertaken to assist Alberta post-secondary institutions with meeting challenges associated with providing services to diverse distributed students that are of similar quality to services provided to traditional classroom students. The first study identified and assessed best practices in distributed learning; the second refined the focus to students who were identified as members of diverse sub-groups. Research activities for the studies included: a comprehensive literature review of best practice in distributed service delivery; an online survey for students enrolled in distributed learning through eight colleges and technical institutes; staff and student focus groups; and interviews with students, front-line staff, senior post-secondary administrators, and representatives from provincial government and community organizations. Findings highlight impressions and experiences in relation to best practice criteria for service delivery in distributed learning, along with “best practices behind the best practices” that facilitate the adoption and improvement of distributed service delivery.